N-Heterocyclic carbene-based gold etchants - Robert B. Chevalier; Justin Pantano; Matthew K. Kiesewetter; Jason R. Dwyer (Beilstein Journal of Nanotechnology, 2023)
N-Heterocyclic carbenes (NHCs) are an emerging alternative to thiols for the formation of stable self-assembled monolayers (SAMs) on gold. We examined several different species that have been used to produce NHC-based monolayers on gold, namely 1,3-diisopropyl-5-nitrobenzimidazolium iodide, 1,3-diisopropyl-5-nitrobenzimidazolium hydrogen carbonate, bis(1,3-diisopropyl-5-nitrobenzimidazolium)gold(I) iodide, and 1,3-diisopropyl-5-nitrobenzimidazole-2-ylidene. Contrary to expectation, solutions containing the first two species in tetrahydrofuran and dichloromethane caused visible loss of gold from thin-film-coated glass slides. The use of toluene solutions of all species resulted in no apparent dissolution of gold. We present scanning electron micrographs and elemental imaging analyses by energy dispersive X-ray spectroscopy to examine the effect of solutions of each species on the gold film. This work highlights the risk of unwanted etching during some routes to NHC-based surface functionalization but also the potential for deliberate etching, with the outcome determined by choice of chemically synthesized organic species and solvent.